Twohundredtwentytwo boys from Stockholm - Jonsson, Gustav; Kälvesten, Anna-Lisa; Andersson, Maja (Stockholm city, 1982)
This survey is an attempt to a social psychiatric mapping of a group of boys growing up in Stockholm. In 1955 the participating boys was tested in a number of different ways. Their development history was mapped through talks with their parents. Their present status, their behaviour and ´manners´ was registred on the basis of interviews with their mothers and teachers. Observations made by physician and psychologist completed the clinical picture. In 1973 the survey was supplemented with data about the boys from a number of registers.

This survey is an attempt to a social psychiatric mapping of a group of boys growing up in Stockholm. In 1955 the participating boys was tested in a number of different ways. Their development history was mapped through talks with their parents. Their present status, their behaviour and ´manners´ was registred on the basis of interviews with their mothers and teachers. Observations made by physician and psychologist completed the clinical picture. In 1973 the survey was supplemented with data about the boys from a number of registers.
222 Stockholmspojkar
Keywords: Youth; Ungdomar; Children; Barn; Social behaviour and attitudes; Socialt beteende och attityder; Social Sciences; Samhällsvetenskap; Sociology; Sociologi